Evaluating the Impact of Modern Laser Technologies on Dentistry in European Union Countries - Chertov, S. O.; Тatarina, O.; Karkimbayeva, G.; Rysbaeva, Z.; Dovzhuk, N.; Чертов, Сергій Олександрович (My University, 2024)
Introduction: in dentistry, understanding laser wavelength interactions with oral tissues enhances patient management. Over two decades, lasers have been used in dental practices for diagnostics, caries detection, calculus identification, hard tissue cutting, and root canal disinfection. They reduce patient anxiety and the need for anesthesia in hard tissue applications. Aim: the objective of this research is to provide a review on how European dentistry has been affected by the use of modern laser technology between 2020 and 2024. This was done by classifying the types of lasers, examining their uses in different dental treatments, investigating the problems that may arise as a result, and appraising the benefits for oral health and patient outcomes. Method: a systematic literature review was conducted from 2020 to 2024, focusing on modern laser technologies in dentistry within European countries. Using the PRISMA flow diagram, studies were identified, screened, and included based on keywords related to dentistry and laser technologies. Initial searches identified 17,130 records, narrowed down to 27 relevant studies through various criteria. Inclusion required studies to focus on dental laser applications in specified European countries, published between 2020 and 2024, and be peer-reviewed. Results: the review covered studies from 2020 to 2024, highlighting various dental specialties and laser technologies like Erbium, CO2, Diode, Nd, Excimer, and Fiber lasers. Findings indicated lasers improved precision, reduced discomfort, and enhanced patient outcomes with minimal postoperative pain and faster recovery times. Noted risks included thermal damage and specific complications like bleeding and pain. Conclusions: the review highlights lasers’ transformative potential in EU dental care, offering precision and improved outcomes. Future research should standardize protocols, assess long-term benefits and risks, focus on safety, and integrate patient-centered outcomes to enhance the evidence base supporting laser technologies in routine dental care.
Keywords: Lasers; Dentistry; Laser Therapy; Dental Care; Dental Health Services; European Union